KOMIK DIGITAL SEBAGAI MEDIA ADVERTISING DI DUNIA VIRTUAL - Khairul Syafuddin (PROGRAM STUDI ILMU KOMUNIKASI, 2020)
Consumer culture formed in society cannot be separated from the role of advertising. With the new media, advertising modes have also evolved. One of them is advertising done through social media Instagram in the form of digital comics. Instagram accounts that utilize digital comic content to produce advertisements are @jukihoki and @ghosty_comic. This research focuses on the discussion of digital comic advertisements, specifically those with the theme of Royale Pass Season 12 PUBG Mobile. The theory used in this study is the psychoanalysis of Sigmund Freud and the political economy of social media in the perspective of Christian Fuchs. The purpose of this study is to determine the grammar connection in digital comic advertisements, the process of advertising the entry of advertisements into the minds of consumers that encourage them to consume, and the practice of political economy social media carried out on Instagram. This study uses qualitative methods with a critical paradigm. In addition, the analysis technique used is the analysis of Charles S. Peirce's semiotics model which focuses on the typology of iconic signs. The results of this study see that digital comics that advertise Royale Pass Season 12 from PUBG Mobile contain social class issues. The issue is put to good use to produce advertisements, it can even encourage consumer psychology to consume the products offered. Even so, in the production of these advertisements there are also elements of political economy social media that are piled up.